* NHS bowel cancer screening programme in england. (13th March 2011) - Coleman, L; Fretwell, I
Abstract : Introduction: NHS Bowel Cancer Screening Programme (BCSP) was established following successful pilot screening programmes in England and Scotland.1 The BCSP commenced in 2006 with a 3-year phased implementation offering screening to men and women aged 60–69. The programme also enabled people aged 70 and over to self-refer into the screening programme. Objectives: (1) Reduce mortality from bowel cancer by up to 16%.2 (2) Offer men and women aged 60–69 a guaiac-based FOBt every 2 years. (3) Enable those over 70 to be screened on request. (4) Offer those with an abnormal screening result a colonoscopy as the investigation of choice. (5) Refer for treatment if cancer is found at screening colonoscopy. (6) Transfer to colonoscopic surveillance within BCSP where intermediate/high risk polyps are found. Methods: The programme comprises five regional programme hubs responsible for call and recall, laboratory processing of test kits and booking clinic appointments for participants with abnormal FOBt results. Participants with an abnormal FOBt result are referred to a local screening centre to discuss colonoscopy with a specialist screening practitioner (SSP) within 2 weeks and offered a screening colonoscopy within a further 2 weeks. Screening centres must satisfy specific criteria: full JAG accreditation of endoscopy units, Global Rating Scale scores of levels A and B and a minimum of two accredited screening colonoscopists. General practitioners are not directly involved in the screening process, but do receive information to support their patients to make an informed choice. Results: All 58 screening centres are now operational across England, and the entire eligible population will have received at least one invitation by December 2011. The screening invitation age range is being extended to 75th birthday from 2010 in response to the government's Cancer Reform Strategy. The eligible screening population will increase from approx 5.3 million to approx 8 million men and women in England. Conclusion: Six million invitations have been despatched. Prevalent round data shows an average uptake of 52.9%. Uptake is lower in men than women, increases with age and falls with increasing levels of deprivation. 2.05% of participants were found to be FOBt positive; 10% of these patients had a confirmed diagnosis of cancer and a further 30% had advanced adenomas and were transferred to colonoscopic surveillance within the screening programme. 61% of cancers found were either staged at Dukes A or B, with a further 10% of cancers being 'polyp cancers' which were completely excised during colonoscopy.